Measurements of the K-shell opacity of a solid-density magnesium plasma heated by an X-ray free electron laser - Preston, T; Vinko, S; Ciricosta, O; Hollebon, P; Preston, T; Chung, H; Dakovski, G; Krzywinski, J; Minitti, M; Burian, T; Chalupský, J; Hájková, V; et al. (American Physical Society, 2017)
We present measurements of the spectrally-resolved X-rays emitted from solid-density magnesium targets of varying sub-μm thicknesses isochorically heated by an X-ray laser. The data exhibit a largely thickness-independent source function, allowing the extraction of a measure of the opacity to K-shell X-rays within well-defined regimes of electron density and temperature, extremely close to local thermodynamic equilibrium (LTE) conditions. The deduced opacities at the peak of the K-α transitions of the ions are consistent with those predicted by detailed atomic-kinetics calculations.